2012
DOI: 10.1007/s12551-012-0084-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of membrane proteins

Abstract: Membrane proteins control the traffic across cell membranes and thereby play an essential role in cell function from transport of various solutes to immune response via molecular recognition. Because it is very difficult to determine the structures of membrane proteins experimentally, computational methods have been increasingly used to study their structure and function. Here we focus on two classes of membrane proteins-ion channels and transporters-which are responsible for the generation of action potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 69 publications
(64 reference statements)
0
5
0
Order By: Relevance
“… 19 Thus, longer simulations are desirable for GPCRs and other membrane proteins. 31 33 Activation that was shown experimentally to occur on millisecond timescales 34 has not been observed in the longest cMD simulations. 25 …”
Section: Introductionmentioning
confidence: 83%
“… 19 Thus, longer simulations are desirable for GPCRs and other membrane proteins. 31 33 Activation that was shown experimentally to occur on millisecond timescales 34 has not been observed in the longest cMD simulations. 25 …”
Section: Introductionmentioning
confidence: 83%
“…For details of the basic formalism of MD simulations, we refer to the monographs [41,42,43]. A recent review of MD simulations of membrane proteins can be found in [44]. …”
Section: Methodsmentioning
confidence: 99%
“…The first protein has a shorter hydrophobic section (namely, KALP 19, 36 The anchoring groups (that is, lysine) at the extremities of the three different protein models are the same to ensure physical consistency. 37 The models for the three proteins are validated through measurements of the tilt of each protein in a membrane along with its impact on the structural characteristics of the bilayer in its vicinity. These measurements require the substitution of four phospholipid molecules in a bilayer (see SI for details) with a single protein.…”
Section: Coarse-grained Model For Proteinsmentioning
confidence: 99%